2012
DOI: 10.1139/x11-188
|View full text |Cite
|
Sign up to set email alerts
|

Early responses to thinning treatments designed to accelerate late successional forest structure in young coniferous stands of western Oregon, USA

Abstract: The loss of critical habitat provided by late successional forests has prompted the search for management options that can accelerate the development of late successional forest structure in young stands. We examined operational-scale commercial thinning treatments at seven sites to evaluate if thinning could accelerate development of late successional forest structures in 40-60 year old Douglas-fir (Pseudotsuga menziesii (Mirb.) Franco) forests. Thinning treatments included an untreated control, high density,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
45
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 65 publications
(56 citation statements)
references
References 35 publications
(60 reference statements)
10
45
0
1
Order By: Relevance
“…As expected, the lower post-treatment densities resulted in increased average tree diameter growth [15,29]. Closer inspection showed that the smaller trees had the highest diameter growth increase.…”
Section: Tree and Stand Growth Responsessupporting
confidence: 73%
See 4 more Smart Citations
“…As expected, the lower post-treatment densities resulted in increased average tree diameter growth [15,29]. Closer inspection showed that the smaller trees had the highest diameter growth increase.…”
Section: Tree and Stand Growth Responsessupporting
confidence: 73%
“…In contrast, diameter growth of larger trees was still higher than those of smaller trees, but increased less or not at all after thinning, unless densities surrounding the trees were very open [15,29]. The spatial variability created, e.g., by including gaps, was also reflected in diameter growth responses, with trees adjacent to gaps showing higher increases in growth [15,30]. Thus, our results suggest that typical thinning treatments are not efficient at achieving tree sizes typically found in old-growth stands (e.g., [31]).…”
Section: Tree and Stand Growth Responsesmentioning
confidence: 74%
See 3 more Smart Citations